2020
DOI: 10.1590/s1984-29612019101
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Toxoplasma gondii in domestic cattle, sheep, goats and pigs from São Tomé and Príncipe

Abstract: Despite the global importance of the zoonotic parasite Toxoplasma gondii, little is known regarding its infection in the Democratic Republic of São Tomé and Príncipe (DRSTP). This is the first report of antibodies to T. gondii in cattle, sheep, goats and pigs from the DRSTP. Antibodies were assessed by the modified agglutination test (MAT), with a cut-off titer of 100 for cattle and 20 for sheep, goats and pigs. The present study revealed an overall seroprevalence of 55.8%; 27.1% in 48 cattle, 68.4% in 98 shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This was in accordance with a study conducted in Mongolia, where young goats of 1-2 years old were found to have a higher T. gondii seroprevalence (39.7%) compared to older animals (3-4 years old, 27.9%; 5-6 years old, 28.3%) [13]. Other studies conducted in Algeria, Pakistan, São Tomé, Bangladesh, and South Africa have demonstrated similar results [14,25,27,28,32,37,38]. This variation could be due to the repetitive exposure of adult animals to oocysts from the environment for a longer period of time than younger animals.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was in accordance with a study conducted in Mongolia, where young goats of 1-2 years old were found to have a higher T. gondii seroprevalence (39.7%) compared to older animals (3-4 years old, 27.9%; 5-6 years old, 28.3%) [13]. Other studies conducted in Algeria, Pakistan, São Tomé, Bangladesh, and South Africa have demonstrated similar results [14,25,27,28,32,37,38]. This variation could be due to the repetitive exposure of adult animals to oocysts from the environment for a longer period of time than younger animals.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a study conducted in Pakistan reported a higher prevalence of T. gondii in goats (42.8%) compared to sheep (26.2%) [34]. Similar findings were also reported in Egypt and São Tomé [14,19]. These were mainly attributed to the husbandry strategy and herding practices of goats since they are allowed greater movement, enhancing their contact with sporulated oocysts sources, whereas sheep are usually housekept and less exposed to parasitic contamination [34].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Among livestock, T. gondii has been found more prevalent in sheep, goats and pigs, than in cattle [4]. Sheep and goats are perceived as biological indicators for the contamination of the environment with sporulated oocysts of T. gondii, because they usually opt for grasses closer to the ground or leaves of shrubs [24][25]. In the present work, the seroprevalence of toxoplasmosis among sheep and goats ranged from 3.98-43.02% in China.…”
Section: Discussionmentioning
confidence: 53%
“…The meta-analysis results suggest that seroprevalence is higher in adult and female animals. It is expected as adult animals are exposed to the T. gondii for longer period of time than the young animals (Bahrieni et al, 2008;Pereira et al, 2020). However, to poor immunity of young animal.…”
Section: Discussionmentioning
confidence: 99%